Neighborhood segregation and urban resource distribution: A path toward sustainability in Ana - Hammad Abdulateef Mohammed (E3S Web of Conferences)
Spatial disparities in resource distribution across urban neighborhoods are a critical factor influencing sustainable urban development. This study investigates the spatial variation of neighborhood characteristics in the city of Ana, focusing on the distribution of social and infrastructural resources. Utilizing geospatial techniques and tools, including Anaconda and Matplotlib, we analyze data from 2024 to assess the accessibility of key urban resources in neighborhoods of varying sizes and population densities. The findings reveal that larger neighborhoods with better infrastructure and social networks exhibit higher resilience and greater access to sustainable resources. In contrast, smaller neighborhoods face compounded challenges, including resource scarcity and spatial segregation, which hinder their contribution to broader urban sustainability goals. These results underscore the need for policymakers to address spatial inequalities and promote balanced resource distribution to support the long-term sustainability and resilience of urban communities.